2001
DOI: 10.1017/s0021932001000876
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mortality and Maternal Health Care in Nepal: Searching for Patterns of Association

Abstract: This study explores the factors associated with neonatal mortality and maternal health care in Nepal. The subjects were 4375 births reported in the 1996 Nepal Family Health Survey. Maternal and child health care was found to have a significant association with neonatal mortality, although preceding birth interval and sex of child had stronger effects. Four aspects of maternal care were found to be highly associated with region, household ownership of assets, mother's education and father's education. This indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 0 publications
6
25
0
Order By: Relevance
“…Our results are in agreement with other studies that showed males had a higher odds of dying than females during the first month of life [36-39]. This increased hazard for newborn males may also be due to the large proportions of neonatal deaths occurring in the first week of life, which is the time when gender differences in neonatal mortality are most pronounced [36]. Biological factors that have been implicated with this increased risk of neonatal death in male infants include immunodeficiency [38] increasing the risks of infectious diseases in males, late maturity [36] resulting in a high prevalence of respiratory diseases in males, and congenital malformations of the urogenital system.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with other studies that showed males had a higher odds of dying than females during the first month of life [36-39]. This increased hazard for newborn males may also be due to the large proportions of neonatal deaths occurring in the first week of life, which is the time when gender differences in neonatal mortality are most pronounced [36]. Biological factors that have been implicated with this increased risk of neonatal death in male infants include immunodeficiency [38] increasing the risks of infectious diseases in males, late maturity [36] resulting in a high prevalence of respiratory diseases in males, and congenital malformations of the urogenital system.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies confirm this, but with varying excess odds [19,23-27]. Contributing factors include immunodeficiency, higher prevalence of respiratory and other infectious diseases, and congenital malformations of the urogenital system [28,29].…”
Section: Discussionmentioning
confidence: 78%
“…Traditionally in Nepalese culture women reside with their husband's family after marriage, and during pregnancy they depend entirely upon their mothers-in-law [9,44] since male involvement in maternity care is not common practice in Nepalese culture [45]. Mothers-in-law are given more responsibility and authority to allocate resources to their daughters-in-law in the belief that they understand women's issues, including health problems.…”
Section: Discussionmentioning
confidence: 99%